Long-term impact of resilience and extraversion on psychological distress during the COVID-19 pandemic: a longitudinal investigation among individuals with and without mental health disorders - Schmit, Anna; Schurr, Timo; Frajo-Apor, Beatrice; Pardeller, Silvia; Plattner, Barbara; Tutzer, Franziska; Conca, Andreas; Fronthaler, Martin; Haring, Christian; Holzner, Bernhard; Huber, Markus; Marksteiner, Josef; et al. (Frontiers in Psychiatry, 2024)
Background: Over the past years, the COVID-19 pandemic has caused significant disruptions in daily routines. Although the pandemic has affected almost everyone, it has been particularly challenging for people with pre-existing mental health conditions. Therefore, this study investigated the long-term impact of resilience and extraversion on psychological distress in individuals diagnosed with mental health disorders (MHD) compared to the general population. In addition, possible gender-specific differences were investigated. Methods: 123 patients with pre-existing MHD and 343 control subjects from Austria and Italy participated in three online surveys that had been conducted after the initial wave of the COVID-19 pandemic (t0), during the second lockdown in both countries (t1), and one year thereafter (t2). Participants completed standardized questionnaires on psychological distress (Brief-Symptom-Checklist), resilience (Resilience Scale), and extraversion (Big Five Inventory). A mediation model was employed to test the primary hypothesis. Possible gender-specific differences were analyzed using a moderated mediation model. Results: The prevalence of psychological distress was consistently higher in patients compared to controls (t0: 37.3% vs. 13.2%, t1: 38.2% vs 11.7%, t2: 37.4% vs. 13.1%). This between-group difference in psychological distress at the first follow-up was fully mediated by baseline resilience scores (65.4% of the total effect). During the second-follow up, extraversion accounted for 18% of the total effect, whereas resilience slightly decreased to 56% of the total effect. Gender was not a significant moderator in the model. Conclusion: Next to showing that people with MHD were particularly affected by the pandemic, these findings indicate that higher degrees of resilience and extraversion are related to less long-term psychological distress. Our findings stress the relevance of strengthening resilience and extraversion and to provide mental health support in times of crises, both to patients with MHD and the general population.